Respuesta :

Answer:

18a - 12

Step-by-step explanation:

6(3a-2)

6*3a - 6*2

18a - 12

Hi there!  

»»————- ★ ————-««

I believe your answer is:  

[tex]18a - 12[/tex]

»»————- ★ ————-««  

Here’s why:  

⸻⸻⸻⸻

[tex]\boxed{\text{Simplifying...}}\\\\6(3a-2)\\-----------------\\\rightarrow \text{Distribute the '6' into '3a' and '-2'.}\\\\\rightarrow 6 * 3a = 18a\\\\\rightarrow 6 * -2 = -12\\\\\\\text{Therefore:}\\\\6(3a-2)\rightarrow \boxed{18a - 12}[/tex]

⸻⸻⸻⸻

»»————- ★ ————-««  

Hope this helps you. I apologize if it’s incorrect.